SIL1, the endoplasmic-reticulum-localized BiP co-chaperone, plays a crucial role in maintaining skeletal muscle proteostasis and physiology - Viraj P. Ichhaporia; Jieun Kim; Kanisha Kavdia; Peter Vogel; Linda Horner; Sharon Frase; Linda M. Hendershot (The Company of Biologists, 2018)
Mutations in SIL1, a cofactor for the endoplasmic reticulum (ER)-localized Hsp70 chaperone, BiP, cause Marinesco-Sjögren syndrome (MSS), an autosomal recessive disorder. Using a mouse model, we characterized molecular aspects of the progressive myopathy associated with MSS. Proteomic profiling of quadriceps at the onset of myopathy revealed that SIL1 deficiency affected multiple pathways critical to muscle physiology. We observed an increase in ER chaperones prior to the onset of muscle weakness, which was complemented by upregulation of multiple components of cellular protein degradation pathways. These responses were inadequate to maintain normal expression of secretory pathway proteins, including insulin and IGF-1 receptors. There was a paradoxical enhancement of downstream PI3K-AKT-mTOR signaling and glucose uptake in SIL1-disrupted skeletal muscles, all of which were insufficient to maintain skeletal muscle mass. Together, these data reveal a disruption in ER homeostasis upon SIL1 loss, which is countered by multiple compensatory responses that are ultimately unsuccessful, leading to trans-organellar proteostasis collapse and myopathy.